2016
DOI: 10.1093/heapro/daw018
|View full text |Cite
|
Sign up to set email alerts
|

Organizational uncertainty and stress among teachers in Hong Kong: work characteristics and organizational justice

Abstract: A growing literature now exists examining the relationship between organizational justice and employees' experience of stress. Despite the growth in this field of enquiry, there remain continued gaps in knowledge. In particular, the contribution of perceptions of justice to employees' stress within an organizational context of uncertainty and change, and in relation to the new and emerging concept of procedural-voice justice. The aim of the current study was to examine the main, interaction and additive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…Furthermore, a series of intensive educational reforms in Mainland China and Hong Kong has been implemented in which teachers are facing increasing academic accountability (Cheng, ; Tan & Chua, ). This, unfortunately, results in that teachers are suffering from a higher level of anxiety and pressure to enhance students' academic achievement and to interact with different stakeholders (Hassard, Teoh, & Cox, ). These highlight the urgency of investigating teacher emotions and its impacts on their teaching in the research sites.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a series of intensive educational reforms in Mainland China and Hong Kong has been implemented in which teachers are facing increasing academic accountability (Cheng, ; Tan & Chua, ). This, unfortunately, results in that teachers are suffering from a higher level of anxiety and pressure to enhance students' academic achievement and to interact with different stakeholders (Hassard, Teoh, & Cox, ). These highlight the urgency of investigating teacher emotions and its impacts on their teaching in the research sites.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported in a study conducted in Russia where instability and uncertainty of organizational changes were identified as causes of stress, innovation fatigue, and emotional burnout 42 . Likewise, a study on Hong Kong teachers revealed employees experience stress during an acknowledged period of organizational uncertainty 43 . The significance of teachers' participation on decision making, for enhancing their organizational roles as professional decision makers, has been emphasized as lack of participation, is expected to result in negative outcomes including stress 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, teacher emotion plays a crucial role in teacher well-being (Fried et al, 2015). Teachers nowadays experience more negative emotions than positive ones (Thompson, 2014; Hassard et al, 2016) and teachers in Asia have been diagnosed and suffer from the same problem of negative emotions in recent years (Chen, 2019). Negative emotions and an inadequate capacity of emotion regulation continues to rank as one of the major reasons for teacher burnout and for teachers leaving their profession (Akin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%